Addressing varenicline adherence through repackaging in a dose administration aid - Drovandi AD; Robertson SG; Malau-Aduli BS; Teague PA; Glass BD (Dove Medical Press, 2017)
Aaron D Drovandi, Sherryl G Robertson, Bunmi S Malau-Aduli, Peta Ann Teague, Beverley D Glass College of Medicine and Dentistry, James Cook University, Townsville, QLD, Australia Background: Ensuring adherence to prescribed smoking cessation medications, such as Champix® (varenicline), is essential during a quit attempt as non-adherence can significantly reduce the likelihood of achieving prolonged smoking abstinence. The use of dose administration aids may improve adherence, though medication stability on repackaging is not guaranteed, due to a lack of available data from manufacturers supporting this practice. Objective: To determine the suitability for repackaging varenicline tartrate tablets into a dose administration aid, by assessing its physical and chemical stability after being repackaged and stored at ambient conditions for 6 weeks. Methods: Varenicline tartrate (1.0 mg) tablets were repackaged into commercially available Webster-pak® blister compartments and stored for 42 days at ambient conditions characteristic of a Zone IVB climate (30 ± 2°C and 75 ± 5% relative humidity) according to the World Health Organization (WHO) guidelines on pharmaceutical stability testing. Physical and chemical tests were performed on the repackaged and control tablets, including an assessment of: tablet thickness, hardness, weight uniformity, friability, dissolution, disintegration, and content uniformity after exposure to ambient conditions and light according to International Council on Harmonisation of Technical Requirements of Pharmaceuticals for Human Use guideline Q1B. Results: Weight, friability, and thickness of the tablets complied with compendial standards. A validated high performance liquid chromatography method was used to confirm that after exposure to light, and repackaging at 30°C/75% relative humidity, the tablets remained within the required 95%–105% of the stated drug content. However, tablet hardness and disintegration decreased over time, with tablets becoming softer and undergoing more rapid disintegration in water. Conclusion: Repackaging 1.0 mg varenicline tartrate tablets into a dose administration aid can be undertaken to improve adherence rates and therefore smoking abstinence rates. This can be performed without compromising either the physical or chemical stability of the tablets. Keywords: stability, compliance, degradation